ENSURING INTERETHNIC HARMONY IS A GUARANTEE OF STABILITY IN THE COUNTRIES OF CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the author intends to widely promote the reputation of the Republic of Uzbekistan in the field of strengthening inter-ethnic harmony and increase its positive image before the world community, cooperation, tolerance, strengthening inter-ethnic harmony in Central Asia and various structures of people, states and society in general. Scientific-theoretical conclusions aimed at further development of friendly relations between representatives of different nationalities and to further increase the kindness and harmony of representatives of different nationalities have been revealed using current sources and published literature.
Keywords: Central Asia, foreign policy, public diplomacy, interethnic harmony, tolerance, friendship societies, national cultural centers.